(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the impact of various pollutants, particularly household waste, on the humus content in soil. Research has shown that different polluting substances, ash residues, as well as heavy metals, plastic waste, and other harmful materials accelerate the decomposition of humus or negatively affect its formation. It has also been established that pollution directly affects the pH and fertility of the soil, disrupting the ecological balance. Changes in humus content were studied under both laboratory and field conditions, and are thoroughly discussed in the article. The research findings contribute to soil protection, restoration, and the development of sustainable agriculture.